Differential Diagnosis of Entamoeba spp. in Clinical Stool Samples Using SYBR Green Real-Time Polymerase Chain Reaction - Thiago dos Santos Gomes; Mariana Coimbra Garcia; Flavia de Souza Cunha; Heloisa Werneck de Macedo; José Mauro Peralta; Regina Helena Saramago Peralta (The Scientific World Journal)
Amoebiasis, a disease caused by Entamoeba histolytica, is usually diagnosed by microscopic examination, which does not differentiate the morphologically identical species of the E. histolytica/E. dispar complex. Furthermore, morphologically similar species such as Entamoeba hartmanni contribute to misidentification. Therefore, there is a need for more sensitive and specific methods. This study standardized a multiplex real-time PCR system for E. histolytica and E. dispar and a single real-time PCR for E. hartmanni. The multiplex protocol detected up to 0.0143 pg of E. histolytica DNA and 0.5156 pg of E. dispar DNA, and the average melting temperature (Tm) was 73°C and 70°C, respectively. For E. hartmanni, the Tm was 73°C and the amplification was successful down to 0.03 fg of plasmid DNA. Negative controls and other intestinal parasites presented no amplification. Among the 48 samples tested, E. dispar DNA was detected in 37; none exhibited E. histolytica DNA and 11 were negative in the multiplex protocol. In 4 of these 11 samples, however, E. hartmanni DNA was amplified. SYBR Green is demonstrated to be an interesting option and these combined PCR reactions can improve laboratory diagnosis of amoebiasis in developing countries.